2020
DOI: 10.3390/en13030561
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Carbon Dioxide Emissions from a Diesel Engine Powered by Lignocellulose Derived Fuel for Better Management of Fuel Production

Abstract: Managing of wastes rich in lignocellulose creates the opportunity to produce biofuels that are in full compliance with the principles of sustainable development. Biomass, as a suitable base for the production of biofuels, does not have to be standardized, and its only important feature is the appropriate content of lignocellulose, which assures great freedom in the selection of input. Biobutanol, obtained from this type of biomass, can be used as fuel for internal combustion engines, including diesel engines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 74 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…However, this process is still hindered by the low butanol yields and the high process costs [306,307]. Thus, recent studies are now using biomass residues (agricultural wastes, lignocellulosic wastes, and industrial wastes) alongside the cellulosic microbes found in various habitats to curb the process costs and pave the way for scale-up studies [308][309][310]. Zhang et al [297] recently used an amylolytic Clostridium species to produce butanol and hydrogen from food waste simultaneously.…”
Section: Butanolmentioning
confidence: 99%
“…However, this process is still hindered by the low butanol yields and the high process costs [306,307]. Thus, recent studies are now using biomass residues (agricultural wastes, lignocellulosic wastes, and industrial wastes) alongside the cellulosic microbes found in various habitats to curb the process costs and pave the way for scale-up studies [308][309][310]. Zhang et al [297] recently used an amylolytic Clostridium species to produce butanol and hydrogen from food waste simultaneously.…”
Section: Butanolmentioning
confidence: 99%
“…The most important renewable liquid fuels are Pure Vegetable Oils (PVO), esters of higher carboxylic acids: methyl Fatty Acid Methyl Esters (FAME), ethyl Fatty Acid Ethyl Esters (FAEE) and alcohols, mainly primary: methanol and ethanol; secondary, alcohol derivatives (mainly ethers); and liquid products of biomass processing Biomass to Liquid (BTL) [162][163][164].…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the amount of particulate matter emitted is therefore a major initiative that has strong support from policy makers around the world [ 8 ]. The emissions can be lowered by installing filters [ 9 ] or by the addition of other compounds that do not produce PM, such as alcohols, including ethanol or butanol [ 10 ], or has overall lower emission levels, such as biodiesel (fatty acid methyl ester—FAME) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%